2020
DOI: 10.3390/ijerph17228452
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and Exercise Performance: With a Focus on Vitamin E and C Supplementation

Abstract: Antioxidant supplementation, including vitamin E and C supplementation, has recently received recognition among athletes as a possible method for enhancing athletic performance. Increased oxidative stress during exercise results in the production of free radicals, which leads to muscle damage, fatigue, and impaired performance. Despite their negative effects on performance, free radicals may act as signaling molecules enhancing protection against greater physical stress. Current evidence suggests that antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
98
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 95 publications
3
98
0
3
Order By: Relevance
“…Similar results have been reported in sport horses [53,56,57,68]. The inconsistency of results regarding the effects of vitamin E supplementation on exercise-induced oxidative stress appears to reflect a variety of factors, including the amount, duration, form, and frequency of vitamin E supplementation; the type and timing of exercise; the age and fitness of the subjects; the vitamin E status of the subjects prior to the studies; and the methodology used to assess oxidative stress [8,41,50,58,66,69]. Nevertheless, it should be emphasised that there is limited evidence to support the use of vitamin E in human athletes [70].…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Similar results have been reported in sport horses [53,56,57,68]. The inconsistency of results regarding the effects of vitamin E supplementation on exercise-induced oxidative stress appears to reflect a variety of factors, including the amount, duration, form, and frequency of vitamin E supplementation; the type and timing of exercise; the age and fitness of the subjects; the vitamin E status of the subjects prior to the studies; and the methodology used to assess oxidative stress [8,41,50,58,66,69]. Nevertheless, it should be emphasised that there is limited evidence to support the use of vitamin E in human athletes [70].…”
Section: Introductionsupporting
confidence: 63%
“…Antioxidant supplementation can have both beneficial and pro-oxidant effects [4,7,44]. In addition, it may hinder or prevent important signalling adaptations to exercise training [12,13,50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been long known that high concentrations of free radicals lead to oxidative damage, it has more recently been shown that the increased ROS levels induced by exercise also play a physiological role [ 17 , 18 , 19 ]. ROS and reactive nitrogen species (RNS) behave as molecular messengers through their interactions with redox-sensitive proteins that regulate processes such as insulin sensitivity, growth factor signaling, vasodilatation, and the immune response [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of single antioxidative sources, it might be speculated that the intake of natural foods rich in antioxidants of phytochemicals (e.g., fruits and vegetables) might represent a more beneficial approach for enhancing the antioxidant status during exercise [ 26 ]. Along with their high antioxidant content, specific diets, including products such as oatmeal, dark chocolate, and mixed fruit beverages may also contain additional bioactive compounds which are not found in single-dose pharmacological antioxidant supplements but can act synergistically to reveal more beneficial effects than a single dose of antioxidant supplements [ 27 , 28 ]. Additionally, these compounds are more accessible than specific isolated antioxidants.…”
Section: Introductionmentioning
confidence: 99%